Advance decisions to refuse treatment and suicidal behaviour in emergency care: 'it's very much a step into the unknown'. Issue 4 (July 2019) - Quinlivan, Leah; Nowland, Rebecca; Steeg, Sarah; Cooper, Jayne; Meehan, Declan; Godfrey, Joseph; Robertson, Duncan; Longson, Damien; Potokar, John; Davies, Rosie; Allen, Neil; Huxtable, Richard; et al.
Abstract : Background: Complex challenges may arise when patients present to emergency services with an advance decision to refuse life-saving treatment following suicidal behaviour. Aims: To investigate the use of advance decisions to refuse treatment in the context of suicidal behaviour from the perspective of clinicians and people with lived experience of self-harm and/or psychiatric services. Method: Forty-one participants aged 18 or over from hospital services (emergency departments, liaison psychiatry and ambulance services) and groups of individuals with experience of psychiatric services and/or self-harm were recruited to six focus groups in a multisite study in England. Data were collected in 2016 using a structured topic guide and included a fictional vignette. They were analysed using thematic framework analysis. Results: Advance decisions to refuse treatment for suicidal behaviour were contentious across groups. Three main themes emerged from the data: (a) they may enhance patient autonomy and aid clarity in acute emergencies, but also create legal and ethical uncertainty over treatment following self-harm; (b) they are anxiety provoking for clinicians; and (c) in practice, there are challenges in validation (for example, validating the patient's mental capacity at the time of writing), time constraints and significant legal/ethical complexities. Conclusions: The potential for patients to refuse life-saving treatment following suicidal behaviour in a legal document was challenging and anxiety provoking for participants. Clinicians should act with caution given the potential for recovery and fluctuations in suicidal ideation. Currently, advance decisions to refuse treatment have questionable use in the context of suicidal behaviour given the challenges in validation. Discussion and further patient research are needed in this area. Declaration of interest: D.G., K.H. and N.K. are members of the Department of Health's (England) National Suicide Prevention Advisory Group. N.K. chaired the National Institute for Health and Care Excellence (NICE) guideline development group for the longer-term management of self-harm and the NICE Topic Expert Group (which developed the quality standards for self-harm services). He is currently chair of the updated NICE guideline for Depression. K.H. and D.G. are NIHR Senior Investigators. K.H. is also supported by the Oxford Health NHS Foundation Trust and N.K. by the Greater Manchester Mental Health NHS Foundation Trust.